1980
DOI: 10.1152/ajpendo.1980.238.5.e416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adrenergic agonists on big and small renin

Abstract: The effect of alpha- and beta-adrenergic agonists on renal and submaxillary renin of different molecular weights was studied using male albino mice as experimental animals. Phenylephrine or isoproterenol was administered intravenously after removal of the submaxillary glands and/or kidneys. Renin was isolated from plasma by column chromatography and then measured by a direct radioimmunoassay. Phenylephrine increased both 68,500-dalton renin (big renin) and 38,000-dalton renin (small renin) in the plasma of nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The elution characteristics of the various forms of renin from plasma of nontreated mice has been reported previously ( 12). semide (control group), the plasma level of big renin was higher than that of small renin.…”
Section: Measurement Of Reninsupporting
confidence: 52%
See 2 more Smart Citations
“…The elution characteristics of the various forms of renin from plasma of nontreated mice has been reported previously ( 12). semide (control group), the plasma level of big renin was higher than that of small renin.…”
Section: Measurement Of Reninsupporting
confidence: 52%
“…Acute stimulation of renin release by furosemide, isoproterenol, tilting, or diazoxide increased active or small renin in human (20, 24), pig (21), dog (18), and mouse (12). Inactive or big renin was not changed in dog by furosemide (18), slightly increased in human by furosemide and isoproterenol (20,24), and greatly increased in pig by furosemide and isoproterenol (21), and in mouse by isoproterenol (12).…”
Section: Measurement Of Reninmentioning
confidence: 98%
See 1 more Smart Citation
“…This is consistent with the findings of earlier studies that reported values of 30% to 50%. 29,30 Although Poulsen and coworkers reported a value of 80% to 90% prorenin for male mice, 31 they commented that the proportion of prorenin measured in the plasma of female mice was around 50%. 32 In the present study, mouse prorenin levels were similarly higher in male than female mice on a normal salt diet, but these differences disappeared in the responses to dietary salt or captopril; none of the differences were significant, possibly due to the small number of males that were tested (9 of 36).…”
Section: Discussionmentioning
confidence: 99%
“…per pg renin, of renin in isoproterenoland phenylephrine-saliva were 0.58 and 0.45 G.U./[i.g, respec¬ tively. Therefore the high molecular weight forms of renin found in plasma from nephrectomized mice (Mailing & Poulsen 1977b;Iwao et al 1980) are probably not secretory pro¬ ducts from the submaxillary gland. /[ig (Pedersen & Poulsen 1981).…”
Section: Discussionmentioning
confidence: 99%